1982
DOI: 10.1111/j.1423-0410.1982.tb00034.x
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and Characterization of Lympho‐Agglutinins in Indian Plants

Abstract: A survey of the occurrence of lympho-agglutinins was carried out on seeds of 150 species of wild and cultivated plants. Potent agglutinins were detected in 17 extracts by employing lymphocytes of man, guinea pig, goat and sheep in the bioassay. Except for one species each of Mimosoideae, Euphorbiaceae and Clusiaceae, all the agglutinins were found in fabaceous seeds. Two of the agglutinins, namely, Parkia biglandulosa and Erythrina arborescens, were found to be monospecific for guinea pig and human lymphocytes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

1982
1982
2006
2006

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 18 publications
2
4
0
Order By: Relevance
“…The present study demonstrates the presence of agglu tinins of varying specificity and potency in 31 plant spe cies, thus corroborating our earlier findings on the com mon occurrence of lympho-agglutinins in Indian plants [16]. Not unexpectedly, the new lectins have a greater association with Fabaceous seeds, although the present study also identified a fairly large number of lectins from non-fabaceous dicotyledonous plants.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…The present study demonstrates the presence of agglu tinins of varying specificity and potency in 31 plant spe cies, thus corroborating our earlier findings on the com mon occurrence of lympho-agglutinins in Indian plants [16]. Not unexpectedly, the new lectins have a greater association with Fabaceous seeds, although the present study also identified a fairly large number of lectins from non-fabaceous dicotyledonous plants.…”
Section: Discussionsupporting
confidence: 80%
“…It is further apparent that in nature, there is a preponderance of those lectins which have an affinity for galactose or its derivatives [6,18]. Since asialofetuin is far more effective as an inhibitor of agglutination, it may be assumed that the availability of multiple galactose moieties along the fetuin peptide chain contributes to better fit than is observed with any specific mono-or disaccharide.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is, however, noteworthy that in case of ruminant species lymphocytes reacted to a larger number of phytolectins than did their erythrocytes [5]. The exact biological significance of these observations is difficult to assess.…”
Section: Discussionmentioning
confidence: 75%
“…The hemagglutinating property was found to be invariably associated with lymphoagglutinins, although not necessarily for the same animal species. However, the opposite may not be always true because in the pres ent study as many as 26 hemagglutinins [5] failed to react with any of the lymphocytes tested. Since lymphocytes usually re sponded to a 10-fold lower dilution of the positive crude extracts than did erythro cytes, it follows that the former may not be as rich in lectin acceptors as are the latter.…”
Section: Methodsmentioning
confidence: 87%